PENGOBATAN GRATIS PADA PENYAKIT PENYAKIT TIDAK MENULAR DI DESA SITIMULYO - Arif Tirtana; Arif Setiawan (LPPM STIKES Madani Yogyakarta, 2019)
Non-communicable diseases is a major cause of death globally. WHO data show that of the 57 million deaths that occurred in the world in 2008, 36 million or nearly two thirds were caused by non-communicable diseases. It also kills residents of a younger age. In countries with low and middle economic levels, of all deaths that occur in people aged less than 60 years, 29% are caused by non-communicable diseases, whereas in developed countries, it causes 13% of deaths. The proportion of deaths is in people aged less than 70 years. Cardiovascular disease is the biggest cause of death (39%), followed by cancer (27%), while chronic respiratory diseases, digestive diseases and other non-communicable diseases together cause around 30% of deaths, and 4% of deaths due to diabetes. More than two thirds (70%) of the global population will die from non-communicable diseases such as cancer, heart disease, stroke and diabetes. In 2030 it is predicted that there will be 52 million deaths per year because of non-communicable diseases. In order to bridge this, the role of health institutions is to provide health facilities to reduce the incidence. The implementation of free medical treatment aims to provide at least the contribution of knowledge and know the health conditions in the community.